Assessment of occupational stress towards turnover intention in construction industry - Kong, Chi Yan (2022)
A high turnover intention in the construction industry is a long-term challenge that brings a lot of negative events to construction companies. This is because the construction industry is very dependent on human capital throughout its process. However, the study on the relationship between Occupational Stressors (OS) and Turnover Intention (TI) are mainly from other industries rather than focusing on the construction industry. Thus, this study aims to examine the potential of occupational stress triggering TI in the Malaysian construction industry. The objectives are (1) identifying the stressors of occupational stress in the construction industry, (2) investigating the relationship between occupational stressors and turnover intention in the construction industry and (3) proposing retention and stress management strategies in the construction industry. This study adopted a quantitative research method by which questionnaire surveys were participated by 270 employees from the Malaysian construction industry with an overall response rate of 77.14%. A total of eleven OS and twelve retention and stress management strategies were identified through a comprehensive literature review and further evaluated in this study. The findings revealed that the five most significant OS among the employees in the Malaysian construction industry are: (1) Pay Level; (2) Working Hours; (3) Work-Life Balance; (4) Work Overload; and (5) Role Conflict while the top five significant retention and stress management strategies were (1) “Provide flexible working hours”; (2) “Have a good working environment”; (3) “Change organizational policy”; (4) “Improve fairness of pay level”; and (5) “Provide compensation package”. This study provides an integrated framework to discuss the relationship between OS, TI and retention and stress management strategies. In short, this study revealed an in-depth investigation of the OS that led to high TI in the Malaysian construction industry which can provide awareness to the construction stakeholders as well as the society in the Malaysian construction industry.